Embracement of the person with mental illness at an emergency hospital service: a qualitative research - Lopes, Paula Fernanda; Melo, Luciana de Lione; Moreno, Vania [UNESP]; Toledo, Vanessa Pellegrino (Assoc Brasileira Enfermagem, 2020)
Objectives: to understand actions of nurses who care for people person with mental illness at a Referenced Emergency Unit in a university hospital. Methods: a qualitative research based on Alfred Schutz's social phenomenology. Data collection was performed between December 2015 and January 2016 through phenomenological interviews with 13 nurses from an Emergency Unit. Results: nurses embrace according to their previous experiences. They easily identify biological complaints and, when they recognize psychiatric signs and symptoms, refer them to the psychiatrist. They raise doubts about what to do, so they expect to be qualified for such action, believing that a protocol could help as well as they need more time. Final considerations: the understanding of the lived type of nurse who embraces people with mental distress made possible in this study need recognition for research and interventions that focus on biological, psychic and social dimension articulation at embracement.
Keywords: Nursing; User Embracement; Mental Health; Emergency Service, Hospital; Qualitative Research